Does Halal Certification Improve MSME Financial Performance? Evidence from Culinary Businesses in Palu City - Nabila Sukmah H; Sitti Aisya; Nursyamsu; Sofyan Bachmid; Fatma; Adib Susilo (Journal of Finance and Islamic Banking, 2026)
Purpose: This study analyzes the role of Islamic financial literacy in shaping the intention of Islamic bank financing farmers, both directly and indirectly through behavioral control. Method: Using a quantitative approach with a survey method of 100 farmers in Pati Regency. The analysis technique uses Partial Least Square-Structural Equation Modeling (PLS-SEM) in the form of the SmartPLS 3 application. Results: These findings show that Islamic financial literacy does not directly encourage intentions, but must first build individual ability, confidence, and control as an intermediary to cause farmers' intentions in applying for Islamic bank financing. Implication: Theoretically, this study strengthens the planned behavior theory model by asserting behavior control as an intention builder. Practically, literacy education must be accompanied by ease of access and simplification of procedures in the agricultural sector. Originality: This study contributed by including perceived behavioral control as a mediating variable. Thus, expanding literature that is still limited to the context of Islamic financial behavior in the agricultural sector.